Erratum. Issue 3 (December 2014) - Unknown
Hedrick, M. S., Lee, J. Y., Harkrider, A., & von Hapsburg, D. (2014) Effects of sentence context on phonemic categorization of natural and synthetic consonant-vowel tokens. Perceptual & Motor Skills: Perception, 118, 1, 210-224. DOI: 10.2466/24.22.PMS.118k14w6 The second author wishes to add a third footnote to the bottom of page 210: 3 Ji Young Lee is currently at the Department of Audiology and Speech-Language Pathology, Catholic University of Daegu, 13-13 Hayang-ro, Hayang-eup, Gyeongsan-si, Gyeongsang-buk-do 712-702 REPUBLIC OF KOREA.